STUDI KOMPARATIF METODE IQRA’ DAN METODE TARTIL TERHADAP KEMAMPUAN MENGENAL HURUF HIJAIYAH BAGI ANAK DISLEKSIA - Beta - Maria (Jurnal Penelitian Pendidikan Khusus, 2014)
Abstract: The research was background by the problems that researcher found in the class Plus Marhamah Padang Elementary School. There are dyslexics recognize hijaiyah letters still low. Iqra’ methods use to improving the reading skills for dyslexic. This study uses a type of quasi-experimental research design with counter balance. Which in this study there were two groups of experimental group and control group were performed in two stages. Each group will get the same treatment. The results of this study is methods Iqra' is more effective in identifying children hijaiyah for dyslexsic class I Plus Marhamah Padang Elementary School.